Development of a health promotion model for modifiying mobile applications among overweight working people in PHRA Nakhon Si Ayutthaya province - Chaiyaser, Panpitcha; Virutsetazin, Kamonmarn (Edelweiss Applied Science and Technology, 2024)
This research and development study aimed to develop and evaluate the effectiveness of a health promotion model for overweight working-age individuals using a mobile application. Phase 1: The preliminary design of the health promotion model was conducted among 110 overweight industrial workers, focusing on dietary and physical activity interventions. Phase 2: The model was further developed and refined through testing with a small sample group of 10 individuals, resulting in a prototype of the health promotion model utilizing the mobile application. Phase 3: The effectiveness of the health promotion model was evaluated through an experimental study involving 45 participants in both the experimental and control groups. Data were analyzed using t-tests. Research Findings, after participating in the program, the experimental group showed statistically significant improvements in dietary behaviors, physical activity, body weight, muscle mass, and fat mass compared to pre-intervention measurements. However, there were no significant changes in their perceived risks or severity of overweight conditions. No significant differences were observed in health behaviors or health status between the experimental and control groups before and after the intervention.